Spliced Peptides and Cytokine-Driven Changes in the Immunopeptidome of Melanoma - Faridi, Pouya; Woods, Katherine; Ostrouska, Simone; Deceneux, Cyril; Aranha, Ritchlynn; Duscharla, Divya; Wong, Stephen Q; Chen, Weisan; Ramarathinam, Sri H; Lim Kam Sian, Terry C C; Croft, Nathan P; Li, Chen; et al. (Cancer immunology research, 2020)
Antigen recognition by CD8 T cells is governed by the pool of peptide antigens presented on the cell surface in the context of HLA class I complexes. Studies have shown not only a high degree of plasticity in the immunopeptidome, but also that a considerable fraction of all presented peptides is generated through proteasome-mediated splicing of noncontiguous regions of proteins to form novel peptide antigens. Here, we used high-resolution mass spectrometry combined with new bioinformatic approaches to characterize the immunopeptidome of melanoma cells in the presence or absence of IFNγ. In total, we identified more than 60,000 peptides from a single patient-derived cell line (LM-MEL-44) and demonstrated that IFNγ induced changes in the peptidome, with an overlap of only approximately 50% between basal and treated cells. Around 6% to 8% of the peptides were identified as -spliced peptides, and 2,213 peptides (1,827 linear and 386 -spliced peptides) were derived from known melanoma-associated antigens. These peptide antigens were equally distributed between the constitutive- and IFNγ-induced peptidome. We next examined additional HLA-matched patient-derived cell lines to investigate how frequently these peptides were identified and found that a high proportion of both linear and spliced peptides was conserved between individual patient tumors, drawing on data amassing to more than 100,000 peptide sequences. Several of these peptides showed immunogenicity across multiple patients with melanoma. These observations highlight the breadth and complexity of the repertoire of immunogenic peptides that can be exploited therapeutically and suggest that spliced peptides are a major class of tumor antigens.